Shu zi zhi shi bao ku zong lan: mei guo shu zi tu shu guan an li jing xi = Surfing the world of knowledge : analytical case studies of digital liberties [libraries] in the United States - 刘燕权; Liu, Yan Quan (Er shi yi shi ji tu shu guan xue cong shu. Di si ji, 2014)
Keywords: Digital libraries; United States; dept.ils; faculty_collection

The Enlightenment of Pew Research Center's Information Management Practice on Academic Library Think Tank Services / 皮尤研究中心信息管理实践对学术图书馆智库服务的启示 - Liang, X.; Liu, Yan Quan (Library & Information, 2019)
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

Information Accessibility, How Far Is It?——An Empirical Research of 146 US Urban Public Libraries / 信息无障碍,距离还有多远?——对146家美国城市公共图书馆的调查 - Guo, Y.; Xi, J.; Liu, Yan Quan (图书馆论坛 [Sun Yat-Sen Library of Guangdong Province], 2020)
文章以美国城市公共图书馆协会146家图书馆为调查对象,借助无障碍评估工具WAVE对这些馆网站主页进行测评,逐一开展网站访查和内容分析,统计为残障用户提供服务的情况。调查发现,美国城市公共图书馆网站达到Section 508信息无障碍标准的比例只有15%,“缺少表单标签”“链接图像缺少替代文本”等是常现错误;55%图书馆网站主页有残障用户服务信息。我国公共图书馆应重视信息无障碍建设,遵循信息无障碍标准,定期进行审查与维护,借助信息无障碍技术提供残障服务。
Keywords: dept.ils; ⛔ No DOI found; 信息无障碍; 公共图书馆; 残障用户; 美国; 调查

An Analytical Study of Recommendation Systems in Chinese City Libraries / 城市图书馆馆藏资源推荐系统调查分析 - Guo, Q; Liu, Yan Quan; Wang, Y (Research on Library Science, 2019)
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

Differences, Complementarity and Convergence of University Library Mobile Service Platforms / 高校图书馆移动服务平台的差异、互补与融合 - Liu, Yan Quan; Zhao, F (Journal of the National Library of China, 2019)
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

The Model and Challenges of Volunteer Service Mechanism in American Urban Libraries / 美国城市图书馆志愿者服务机制模式及面临的挑战 - Ren, X; Liu, Yan Quan (Library & Information, 2019)
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

Current situation and development trends of mobile services in the United States' urban libraries - Guo, Y; Liu, Yan Quan (Library and Information, 2018)
Keywords: dept.ils; ⛔ No DOI found

The latest study of digital virtual reference service in Chinese top university libraries - He, X; Wang, Y; Liu, Yan Quan (Journal of Intelligence, 2017)
Keywords: dept.ils; ⛔ No DOI found

The latest study of reading promotion activities in American public libraries - He, X; Wang, Y; Liu, Yan Quan (Library and Information, 2017)
Keywords: dept.ils; ⛔ No DOI found